Hidden Symmetries of Rationally Deformed Superconformal Mechanics - Pliouchtchai, M; Inzunza-Melo, L (American Physical Society, 2019)
We study the spectrum generating closed nonlinear superconformal algebra that describes N=2 superextensions of rationally deformed quantum harmonic oscillator and conformal mechanics models with coupling constant g=m(m+1), mN. It has a nature of a nonlinear finite W superalgebra being generated by higher-derivative integrals and generally contains several different copies of either deformed superconformal osp(2|2) algebra in the case of superextended rationally deformed conformal mechanics models or deformed super-Schrödinger algebra in the case of the superextension of rationally deformed harmonic oscillator systems. © 2019 authors. Published by the American Physical Society.